Consideraciones de diseño de cimentaciones tipo pórtico para equipos dinámicos (2014)
The foundations of machines are a fundamental part of any industrial complex. This paper presents the main considerations and design criteria for projecting safe and efficient foundations. The difference with conventional foundations lies in the dynamic analysis that must be developed to ensure that the frequencies of the machine-foundation system are different from the normal operating frequency of the machine and that the amplitudes of the system are framed within the admissible limits. As a complement, this This work presents a practical example where the behavior of a gantry type foundation for a turbogenerator is studied, which is dimensioned and its analysis and design is carried out. The example is developed analytically and by finite elements using a computational tool of design. Finally, comparisons of the theoretical and experimental results were made with excellent approximations. The results obtained are shown sequentially to facilitate their understanding and the content is arranged to present to the reader the importance of the measurement of vibrations in the equipment-foundations system. The idea is that the reader understands the practical meaning of the frequencies and amplitudes in the analysis gantry type for dynamic equipment. The present work was justified because it has a practical value and educational relevance. In addition, strong foundations were established to familiarize the student with the design of dynamic equipment, showing that today the technology establishes better performance when performing mathematical models but always with the caution and aware that a good characterization of the input data must be obtained.